The sublime, or the exposable (Itinera, 2021)
The paper reconsiders the possibility of understanding the art of avant-garde in the light of the sublime, as argued by Jean-François Lyotard in his famous critical essay on Barnett Newman’s artwork Vir Heroicus Sublimis. According to the paper, the scope of a ‘sublime art’ of the avant-garde is larger than the reference to a single artist or movement, and entails the possibility of comprehending the reflective stance of modernism as a critique, performed by art, of the conditions of possibility of exposition as a gesture that is relevant not only to the art world but to experience at large. The sublime art brings this critique to its extreme consequences as far as it explores the boundaries of exposition with regard to the world image supplied by the media system. This sublime directory of the avant-garde was inaugurated by Marcel Duchamp as he introduced the practice of the ready-media in the art system. However, it enjoyed a long-lasting success thereafter.
Keywords: Sublime; Avant-garde; Exposition; Lyotard.